Turkey (Organisation for Economic Co-operation and Development, 2008)
The report presents a review of the Turkish health system. Intended for professional public.
OECD reviews of health systems
Keywords: Turkey; Delivery of Health Care; Turecko; průzkumy zdravotní péče; Health Care Surveys; poskytování zdravotní péče; kvalita zdravotní péče; Quality of Health Care; veřejné zdravotnictví